2015
DOI: 10.33073/pjm-2015-015
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Pseudomonas aeruginosa PA01 intercellular signaling pathway (Quorum Sensing) functioning in presence of porphyrins bismuth complexes

Abstract: The influence of synthetic and natural porphyrins bismuth complexes on P. aeruginosa quorum sensing system was carried out by detection of the pyocyanin, rhamnolipids and autoinducers biosynthesis level. The highest ability to reduce pyocyanin biosynthesis showed Bi(III)-TPP. Rhamnolipids production level also decreased in the presence of studied compounds. This effect was the most expressed in presence of 40 and 80 µM of the synthetic meso-substituted porphyrins. Autoinducers biosynthesis, especially 3-oxo-C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Production of QS inhibitors can have a role in securing a foothold in a surface environment by inhibiting the attachment of marine bacteria, and consequently of larvae, algae and barnacles (Goecke et al, 2010;Wahl et al, 2010). Described QS inhibitors include furanones and their analogs (Zang et al, 2009), bismuth porphyrin complexes (Galkin et al, 2015) or glycosylated flavonoids (Brango-Vanegas et al, 2014). A study demonstrated that kojic acid inhibited QS activity and formation of microbial communities on glass slides, decreasing both the densities of bacteria and diatoms (Dobretsov et al, 2011).…”
Section: Induction Of Larval Settlementmentioning
confidence: 99%
“…Production of QS inhibitors can have a role in securing a foothold in a surface environment by inhibiting the attachment of marine bacteria, and consequently of larvae, algae and barnacles (Goecke et al, 2010;Wahl et al, 2010). Described QS inhibitors include furanones and their analogs (Zang et al, 2009), bismuth porphyrin complexes (Galkin et al, 2015) or glycosylated flavonoids (Brango-Vanegas et al, 2014). A study demonstrated that kojic acid inhibited QS activity and formation of microbial communities on glass slides, decreasing both the densities of bacteria and diatoms (Dobretsov et al, 2011).…”
Section: Induction Of Larval Settlementmentioning
confidence: 99%
“…The molecules responsible for inhibition of autoinducer-induced QS systems or the autoinducer-regulated phenotype are called quorum-sensing inhibitors (QSIs). QSIs include furanones and their related structural analogs (Figure 2E ; Zang et al, 2009 ; Liu et al, 2010 ; Steenackers et al, 2010 ), bismuth porphyrin complexes (Galkin et al, 2015 ), glycosylation reagents of glycosylated flavonoids (Figure 2F ; Brango-Vanegas et al, 2015 ), and glycomonoterpenols (Mukherji and Prabhune, 2015 ), heavy metals (Vega et al, 2014 ) and nanomaterials (Wagh Nee Jagtap et al, 2013 ; Miller et al, 2015 ; Singh et al, 2015 ). The inhibitory effect of furanones is primarily due to their structural similarity to AHLs, but some case studies also showed that furanones may function through degrading the LuxR-type protein (Manefield et al, 2002 ) or decreasing the DNA-binding activity of the transcriptional regulator protein LuxR (Defoirdt et al, 2007b ).…”
Section: Inhibition and Activation Of Qs Systems In Gram-negative Bacmentioning
confidence: 99%